2018
DOI: 10.1111/ijfs.13844
|View full text |Cite
|
Sign up to set email alerts
|

Effect of protease inhibitors on proteolytic degradation of rohu (Labeo rohita) gel

Abstract: Summary Endogenous proteases are responsible for gel weakening of fish muscle protein. We investigated inhibitory effect of four selected protease inhibitors: soya bean trypsin inhibitor, leupeptin, E64 and EDTA, to identify the protease groups responsible for gel degradation in both unwashed and washed rohu (Labeo rohita) gel. The protease inhibitory activity was determined by percentage inhibition and SDS‐PAGE pattern. Leupeptin and E64 showed a strong inhibition on the autolysis of unwashed gel, and myosin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…ly. This supported the results from our previous studies, which suggested that the degradation of washed rohu gel was caused by serine protease [27]. Thus, the ovoinhibitor, one of the proteinase inhibitors in EW, could inhibit serine proteinase in washed rohu gel.…”
Section: Effect Of Ew On Expressible Water Contentsupporting
confidence: 91%
“…ly. This supported the results from our previous studies, which suggested that the degradation of washed rohu gel was caused by serine protease [27]. Thus, the ovoinhibitor, one of the proteinase inhibitors in EW, could inhibit serine proteinase in washed rohu gel.…”
Section: Effect Of Ew On Expressible Water Contentsupporting
confidence: 91%
“…On the other hand, the unfolding of myofibrillar protein induced by HPP might expose more positively charged sites to carrageenan, resulting in a stronger gum–protein interactions (Chen et al, ). In addition, the activity of endogenous protease is an important factor affecting the gel strength of surimi (Sutloet et al, ). The endogenous transglutaminase (TG) in surimi could catalyze proteins cross‐linking via the formation of covalent glutamyl–lysine cross‐links between glutamine and lysine of fish proteins (Zhu et al, ), and a prior HPP treatment might render greater access of TG to the targeted glutamine and lysine residues, thereby promoting intermolecular cross‐link formation and improving gel strength (Chen et al, ; Truong et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Freshwater fish have been utilized as alternatives for surimi production owing to the decline in marine fishery resources (Sutloet, Sompongse, & Morioka, ). Silver carp ( Hypophthalmichthys molitrix ), as an important freshwater fish species, is widely used in surimi products due to its abundance and moderate price as well as high nutritional value (Barrera, Ramırez, González‐Cabriales, & Vázquez, ).…”
Section: Introductionmentioning
confidence: 99%
“…Ramirez et al (2002) found when Mexican flounder and Atlantic croaker surimi were incubated at 60 • C for 3 h, the actin showed practically no change, even though the MCH band almost disappeared. Sutloet et al (2018) also found no changes of actin intensity among rohu gels made with or without protease inhibitors. Interestingly, Yongsawatdigul & Piyadhammaviboon (2004) observed pronounced degradation of actin and tropomyosin when lizardfish surimi was incubated at 65 • C for 1 h. Takahashi et al (2016) found a drastic decrease of actin band intensity when unwashed filefish meat was heated at 60 • C for 120 min.…”
Section: Notementioning
confidence: 81%
“…Abbreviations: AC, action; FPI, fish protein isolate paste without soy whey added; M, molecular mass marker; MCH, myosin heavy chain; T, commercial soybean trypsin inhibitors; TM, tropomyosin; W, soy whey making from sardine surimi, TCA-soluble peptide content decreased with increased amount of black bean and mungbean protein isolates up to 1%, after which, no further decrease of TCA-soluble peptide content was found. Sutloet et al (2018) found during gelation of rohu gel, purified soybean trypsin inhibitor (inhibitor toward serine proteases), leupeptin (inhibitor toward both serine and cysteine proteases), butane (inhibitor toward cysteine protease), and EDTA (inhibitor toward metalloproteases) each achieved its highest possible inhibition between 50% and 80%, after which, no further inhibition could be found. Our data in combination with the data by other researchers indicated that a single inhibitor alone was not enough to achieve a complete inhibition of proteolysis due to the presence of multiple types of proteases.…”
Section: F I G U R Ementioning
confidence: 99%